Sustainability in photography can change the world - Scott, Rowena (IGI Global, 2014)
Photography plays important, but undervalued and misunderstood, roles in how modern urban humans relate to nature and how nature is mediated to us, forming our perceptions and national identity. Typically landscape photography depicts nature aesthetically as sublime, picturesque and beautiful. Photographs have been powerful raising awareness of sustainability and communicating political messages. The chapter reviews the influence of two great Australian wilderness photographers, Olegas Truchanas and Peter Dombrovskis, as well as Edith Cowan University’s (ECU) Photography for Environmental Sustainability Competition. In conjunction with World Environment Day, the university invited students to submit photographs that showcase the principles and practices of environmental sustainability. This chapter describes the history, purposes and impact of photography and the competition. Starting as an engagement partnership between the environment coordinator, academics and the Perth Centre for Photography, it is now an international competition across Australia and New Zealand, not exclusive to photography students, hosted by Australasian Campuses Towards Sustainability (ACTS).